EFFECT TO MOTIVATION AND WORK EXPERIENCE IN THE PERFORMANCE OF EMPLOYEES PT. PERKEBUNAN NUSANTARA II (PERSERO) TANJUNG MORAWA - Indra, Aulia (Published by the Faculty of Economics and Business, University of Labuhanbatu, North Sumat, 2019)
Motivation of employees in an organization can be considered simple and can also be a complex problem, because basically humans easily motivated by giving what is his desire. Problems employee motivation can be difficult to determine what remuneration which is considered essential for one is not necessarily important for others. With the motivation to work, it can be seen the effect of the performance of the employee in which the employee will act on the basis kainginan to excel and gain higher positions in the company. The purpose of this research is to analyze the influence of motivation and work experience to employees performance at PT. Perkebunan Nusantara II (Persero) Tanjung Morawa. This research is a quantitative correlation study. The population in this study was 452 and sampled is 82 people. Data collection techniques used through interviews, documentation and questionnaires. The analytical method used is multiple linear regression. The results showed that in partial motivation (X1) but not significant effect on employee performance (Y). Partial variable work experience (X2) positive and significant impact on employee performance (Y). Simultaneously motivation variable (X1) and work experience (X2) positive and significant impact on employee performance (Y). The coefficient of determination of 37% indicates that the motivation (X1) and work experience (X2) as the independent variables are able to explain the variable performance of employees, while the remaining 63% is explained by other factors that are not included in this study.